2022
DOI: 10.3390/foods11182840
|View full text |Cite
|
Sign up to set email alerts
|

Current Sex Distribution of Cooking and Food Shopping Responsibilities in the United States: A Cross-Sectional Study

Abstract: Home cooking is an important obesity prevention strategy and associated with benefits for diet and health. Although cooking may be a joyful act of mindfulness, it also requires planning, preparation and time. Historically, women have been more likely to fulfill the role of food shopping and cooking. More recent studies suggested a transition in traditional household role assignments towards a larger involvement of males. This study examined the current sex distribution of cooking and food shopping responsibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The 1990s data indicated women as primarily responsible for family meal tasks, and the 2020 data indicated that more men were involved and taking some degree of responsibility for these tasks. However, the gendered divide of responsibility remained in some 2020 households regardless of dual-employment status, aligning with recent literature ( Burnod et al, 2022 ; Storz et al, 2022 ). Furthermore, as we did not observe these practices, we cannot definitively state that men’s participation has increased, but that the discourse between couples and the presentation of family meal practices may have changed.…”
Section: Discussionsupporting
confidence: 85%
“…The 1990s data indicated women as primarily responsible for family meal tasks, and the 2020 data indicated that more men were involved and taking some degree of responsibility for these tasks. However, the gendered divide of responsibility remained in some 2020 households regardless of dual-employment status, aligning with recent literature ( Burnod et al, 2022 ; Storz et al, 2022 ). Furthermore, as we did not observe these practices, we cannot definitively state that men’s participation has increased, but that the discourse between couples and the presentation of family meal practices may have changed.…”
Section: Discussionsupporting
confidence: 85%
“…These identifiers were specifically chosen as they are considered the most important according to the literature review, e.g., [ 38 , 42 , 45 , 46 , 48 ]. More women were selected for the research because historically, women have been more likely to fulfil the role of food shopping [ 58 ]. Moreover, in the area of incomes, a larger representation of customers with wages between 30,001–40,000 CZK was selected because in 2020 the median of wages in the Czech Republic is in this interval [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…This finding may be attributed to several factors, including higher levels of nutrition knowledge [ 12 , 16 ], greater awareness of the importance of reading food labels [ 12 ], and the higher prevalence of dieting and eating disorders [ 47 ] among women. In addition, the fact that grocery shopping is usually done by women [ 48 ] it may be a possible explanation for this result, as those responsible for grocery shopping were found to be more likely to be users of food labels [ 21 ]. Furthermore, having children was associated with using the ingredients list and claims sections of food labels.…”
Section: Discussionmentioning
confidence: 99%